An induced pluripotent stem cell line, NIMHi014-A, generated from PBMCs of an epileptic patient harbouring a variant of the SCN1A gene - Madhura Milind Nimonkar; Gautham Arunachal; Ananthapadmanabha Kotambail; Ramya Sukrutha; Kenchaiah Raghavendra; Ghati K Chetan; Bhupesh Mehta; Yogananda S. Markandeya (Stem Cell Research)
We report the iPSC line NIMHi014-A, generated from the PBMCs of an epileptic girl child. The proband harbours a de novo, pathogenic variant of the SCN1A gene, which encodes the NaV1.1 subtype of the voltage gated sodium channel. The cell line NIMHi014-A displayed typical iPSC-like morphology, expressed stemness markers and possessed trilineage differentiation potency. The cells presented a normal karyotype and had no mycoplasma contamination. This cell line will be used to study mechanism of epilepsy and develop patient specific therapies.